TERRITORIAL RISK ASSESMENT AFTER TERRORIST ACT: EXPRESS MODEL - Biliaiev, M. M.; Kalashnikov, I. V.; Kozachyna, V. A. (Science and Transport Progress, 2021)
Purpose. The paper involves the development of a method to assess the territorial risk in the event of a terrorist attack using a chemical agent. Methodology. To describe the process of chemical agent scattering in the atmosphere, ejected in the event of a terrorist attack, the equation of mass transfer of an impurity in atmospheric air is used. The equation takes into account the velocity of the wind flow, atmospheric diffusion, the intensity of chemical agent emission, the presence of buildings near the site of the emission of a chemically hazardous substance. For numerical integration of the modeling equation, a finite difference method is used. A feature of the developed numerical model is the possibility of assessing the territorial risk in the event of a terrorist attack under different weather conditions and the presence of buildings. Findings. A specialized numerical model and software package has been developed that can be used to assess the territorial risk, both in the case of terrorist attacks, with the use of chemical agents, and in case of extreme situations at chemically hazardous facilities and transport. The method can be implemented on small and medium-sized computers, which allows it to be widely used for solving the problems of the class under consideration. The results of a computational experiment are presented that allow estimating possibilities of the proposed method for assessing the territorial risk in the event of a terrorist attack using a chemical agent. Originality. An effective method of assessing the territorial risk in the event of a terrorist attack using a chemically hazardous substance is proposed. The method can be used to assess the territorial risk in an urban environment, which allows you to obtain adequate data on possible damage areas. The method is based on the numerical integration of the fundamental mass transfer equation, which expresses the law of conservation of mass in a liquid medium. Practical value. The proposed method for assessing the territorial risk in the event of a terrorist attack using a chemical agent can be used to calculate the affected areas near administrative buildings, centers and other socially significant facilities.